The Pharmacokinetics and Lipoprotein Fraction Distribution of Intramuscular vs. Oral Vitamin K1Supplementation in Women of Childbearing Age: Effects on Hemostasis - Hagstrom, J Nathan; Bovill, Edwin G; Soll, Roger F; Davidson, Kenneth W; Sadowski, James A (Thrombosis and Haemostasis, 1995)
Prenatal maternal vitamin K1 supplementation to improve the hemostatic status of the fetus may depend upon the route of administration and subsequent presentation at the placental barrier. We investigated intramuscular (IM) vs oral (PO) vitamin K1 supplementation in eight healthy, nonpregnant women of childbearing age. Pharmacokinetics were studied in each subject after a 5 mg IM dose and after a 5 mg oral dose of vitamin K1 approximately one month later. Plasma collected at the peak vitamin K level for each treatment was separated into very low density lipoproteins (VLDL), low density lipoprotein (LDL), high density lipoprotein (HDL) and lipoprotein-free fractions by density gradient ultracentrifugation. Vitamin K1 was measured in the plasma and lipoprotein fractions using HPLC. The concentration of vitamin K1, in plasma reached a peak 2 h after an IM dose and remained high throughout the 30 h course of the study. In contrast, the oral dose of vitamin K1 peaked at 4 h and rapidly decreased to near baseline by 18 to 30 h. The distribution of vitamin K1 in the lipid fractions was different for IM compared to PO. The percentage of vitamin K1 in the VLDL fraction at the peak for an oral dose was significantly higher than for an IM dose (80.8% ± 3.5 vs 10.8% ± 6.5, p <0.0001). After the oral absorption stage, the subjects took 5 mg of vitamin K1 orally, once a day, for 12 days. No significant differences were observed for the following coagulation proteins and hemostatic markers measured immediately before and after long-term oral vitamin K supplementation: factor II, factor VII, protein C, and thrombin-antithrombin III complex. In conclusion, physiological processing of supplemented vitamin K1 differs in the IM vs PO routes of administration and 12 days of oral vitamin K1does not alter the concentration of selected vitamin Independent coagulation proteins or thrombin-antithrombin complex generation